Sayonara - Dennis M Bowie (Canadian Respiratory Journal)
It is with mixed feelings that I write this last page. There is some relief in handing over the responsibilities to someone else, although I will miss the interaction with all the good people that I have met from across Canada who have made me a part of their lives. I want to take the opportunity to point out what the Canadian Thoracic Society (CTS), through its volunteer members and, in particular, its hard working committees, has accomplished in the past year.